The role of hormone therapy before hysteroscopic myomectomy - Antonio Simone Laganà; Susan Dababou; Mariachiara Bosco; Pier Carlo Zorzato; Paola Pomini; Rossana Di Paola; Stefano Uccella; Ricciarda Raffaelli; Massimo Franchi (IMR Press, 2021)
Objective: This review analyzes the preoperative treatments used before hysteroscopic myomectomy, trying to identify the main indications for each option. Methods: a comprehensive search of several databases was conducted from inception up to May 2021. The searched databases were MEDLINE, In-Process & Other Non-Indexed Citations, Daily, Ovid EMBASE, Cochrane Central Register of Controlled Trials, Cochrane Database of Systematic Reviews, and Scopus. The search strategy included the combinations of the following medical terms: Hysteroscopic myomectomy; Uterine fibroid, Hormonal therapy, preoperative. We selected clinical studies, systematic reviews, and meta-analyses in English to investigate hormone therapy before hysteroscopic myomectomy. We opted for a narrative synthesis of the results, summarizing the evidence provided by the most relevant studies to offer the reader a complete and synthetic overview of the topic. Findings in brief: The hormonal therapies preoperatively used to prepare the endometrium before a hysteroscopic procedure are gonadotropins releasing hormone (GnRH) analog, danazol, progestogen, and combined oral contraceptives. On the one hand, the efficacy of GnRH analogs and danazol administration before hysteroscopic surgery has been demonstrated by several studies, mainly related to the time of surgery and volume of distension medium absorbed. On the other hand, although the evidence is more limited, progestogens and combined hormonal contraceptives have proven a comparable efficacy in achieving adequate endometrial thinning. Conclusions: To date, no definitive data provide strong evidence towards one specific preoperative therapy before myomectomy hysteroscopy. Several variables should be considered using a specific medical therapy (including the different potential effects with a particular drug compared to the others in type 0, 1, or 2 myoma); this element further amplifies the heterogeneity of the available findings in the literature and does not allow to draw a firm conclusion about a best pharmacological management over the others.